2009
DOI: 10.1017/s1368980009992783
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of eating away-from-home meals and weight gain in a Mediterranean population: the SUN (Seguimiento Universidad de Navarra) cohort

Abstract: Objective: The traditional Mediterranean food pattern is more easily preserved when meals are eaten at home; however, as a result of recent socio-economic changes, away-from-home meal consumption has increased rapidly in Mediterranean countries. Little research has been conducted so far to investigate the long-term health effects of these changes in the Mediterranean area. Design: In a prospective Spanish dynamic cohort of 9182 university graduates (the SUN Study; Seguimiento Universidad de Navarra, University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 39 publications
5
92
0
3
Order By: Relevance
“…Many studies have analyzed eating location to compare meals made at home and away from home, types of restaurants, or consumed foods [18][19][20][21] . Even Brazilian studies have failed to analyze meals consumed at work cafeterias.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have analyzed eating location to compare meals made at home and away from home, types of restaurants, or consumed foods [18][19][20][21] . Even Brazilian studies have failed to analyze meals consumed at work cafeterias.…”
Section: Discussionmentioning
confidence: 99%
“…In six years (2002/2003-2008/2009) the participation of away-from-home foods in food expenditures in urban areas increased from one-fourth (25.7%) to one-third (33.1%), and in rural areas, from 13.1% to 17.5%. In 2008 the mean intake of away-from-home calories corresponded to approximately 16.0% of the total calorie intake and was greater in males and individuals with higher income per family member from urban areas of the Brazilian Southeast Away-from-home foods have higher energy density, fat content, and saturated fat content; and lower micronutrient content [3][4][5][6][7][8][9][10] . Gorgulho et al 10 assessed the quality of homemade and away-from-home meals in the municipality of São Paulo and found that the latter had lower nutritional quality, potentially contributing to the development of chronic Noncommunicable Diseases (NCD) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The growing rates of overweight seen in the last decades have been associated with the number of meals away from home [3][4][5][6][7][8][9]11 . Bezerra & Sichieri 11 showed that the prevalences of overweight and obesity in men who eat away from home (38.5% and 11.9%, respectively) were higher than the prevalences in men who do not (36.1% and 10.3%, respectively) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several publications on eating out and obesity that make use of cross-sectional [3][4][5][6][7][8][9][10][11][12][13][14][15] and longitudinal data. 5,11,16,17 Results, however, have been inconsistent, probably because of different definitions used and variable study objectives. Eating out was either defined to include all food items prepared at out-of-home locations, irrespective of place of consumption; 3,[7][8][9][10] or alternatively, all food items consumed at out-of-home locations, irrespective of place of preparation.…”
Section: Introductionmentioning
confidence: 99%